2010
DOI: 10.1262/jrd.09-158a
|View full text |Cite
|
Sign up to set email alerts
|

Production of Sei Whale (Balaenoptera borealis) Cloned Embryos by Inter- and Intra-Species Somatic Cell Nuclear Transfer

Abstract: Abstract. The objectives of this study were to choose an effective embryo reconstruction method and an effective postactivation agent for in vitro production of sei whale (Balaenoptera borealis) interspecies somatic cell nuclear transfer (iSCNT) embryos. Moreover, trichostatin A (TSA) treatment of whale iSCNT embryos was performed to improve the in vitro embryo development. In Experiment 1, the fusion rate was significantly higher (88.1%) in embryos reconstructed using the intracytoplasmic cell injection metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 39 publications
0
4
1
Order By: Relevance
“…Therefore, reduction of the development of iSCNT cat embryos may result in part from the exposure of TSA with a high concentration. In contrast to our results, TSA treatment has been shown to have no effects on the embryonic development of iSCNT, e.g., guar-cow (Srirattana et al, 2012), human-rabbit (Shi et al, 2008), and sei whalecow (Bhuiyan et al, 2010). The difference in results might be associated with the TSA applications (concentration, timing, and the onset of treatment), species-specific effects, and phylogenetic distance between the oocyte and somatic cell donor.…”
Section: Figcontrasting
confidence: 99%
“…Therefore, reduction of the development of iSCNT cat embryos may result in part from the exposure of TSA with a high concentration. In contrast to our results, TSA treatment has been shown to have no effects on the embryonic development of iSCNT, e.g., guar-cow (Srirattana et al, 2012), human-rabbit (Shi et al, 2008), and sei whalecow (Bhuiyan et al, 2010). The difference in results might be associated with the TSA applications (concentration, timing, and the onset of treatment), species-specific effects, and phylogenetic distance between the oocyte and somatic cell donor.…”
Section: Figcontrasting
confidence: 99%
“…Interspecies SCNT (iSCNT) where endangered animal somatic cell nuclei are transferred to domestic oocyte cytoplasts is an approach that might minimize the limitations of SCNT. Many trials of iSCNT have been reported in wildlife species such as the giant panda ( Ailuropoda melanoleuca ) [ 6 , 7 ], Tibetan antelope ( Pantholops hodgsonii ) [ 8 ], Banteng ( Bos javanicus ) [ 9 ], yak ( Bos grunniens ) [ 10 ], Siberian tiger ( Panthera tigris altaica ) [ 11 ], and Sei whale ( Balaenoptera borealis ) [ 12 ]. The iSCNT cloned embryos generated in these studies had extremely poor development to the blastocyst stage.…”
Section: Introductionmentioning
confidence: 99%
“…Both intracytoplasmic cell injection (ICI) and subzonal cell insertion (SUZI) are equally effective with respect to PPN formation and cleavage of sei whale iSCNT embryos. Bovine oocytes have the ability to support development of sei whale nuclei up to the 6-cell stage (Bhuiyan et al ., 2010). Sei whale iSCNT embryos can also be reconstructed using porcine oocytes.…”
Section: Whale Interspecies Somatic Cell Nuclear Transfermentioning
confidence: 99%
“…The high rates of developmental blockage in whale iSCNT might be due to failure in timely activation of the whale embryonic genome. Further studies are needed on reprogramming mechanism of whale nuclei at the molecular level to gain a better understanding of development in iSCNT embryos (Bhuiyan et al ., 2010). Thus, development of iSCNT embryos may provide some information about whale embryo development.…”
Section: Whale Interspecies Somatic Cell Nuclear Transfermentioning
confidence: 99%